RIPK1-Associated Inborn Errors of Innate Immunity - Zhang, Jiahui; Jin, Taijie; Aksentijevich, Ivona; Zhou, Qing (Frontiers in Immunology, 2021)
RIPK1 (receptor-interacting serine/threonine-protein kinase 1) is a key molecule for mediating apoptosis, necroptosis, and inflammatory pathways downstream of death receptors (DRs) and pattern recognition receptors (PRRs). RIPK1 functions are regulated by multiple post-translational modifications (PTMs), including ubiquitination, phosphorylation, and the caspase-8-mediated cleavage. Dysregulation of these modifications leads to an immune deficiency or a hyperinflammatory disease in humans. Over the last decades, numerous studies on the RIPK1 function in model organisms have provided insights into the molecular mechanisms of RIPK1 role in the maintenance of immune homeostasis. However, the physiological role of RIPK1 in the regulation of cell survival and cell death signaling in humans remained elusive. Recently, RIPK1 loss-of-function (LoF) mutations and cleavage-deficient mutations have been identified in humans. This review discusses the molecular pathogenesis of RIPK1-deficiency and cleavage-resistant RIPK1 induced autoinflammatory (CRIA) disorders and summarizes the clinical manifestations of respective diseases to help with the identification of new patients.